‘Setting the Benchmark’ Part 4: Contextualising the Match Demands of Teams at the FIFA Women’s World Cup Australia and New Zealand 2023 - Bradley, Paul S. (Biology of Sport, 2025)
The aims of the present study were to: (1) analyse the upper and lower match physical performance benchmarks and variability of teams at the FIFA Women’s World Cup Australia and New Zealand 2023, (2) examine the evolving team sprint ranking across three Women’s World Cups and (3) investigate noteworthy relationships between collective physical and tactical metrics. With FIFA’s official approval, all sixty-four games at the tournament were analysed using an optical tracking system alongside FIFA’s Enhanced Football Intelligence metrics. On average, teams at the FIFA Women’s World Cup 2023 covered 103.3 ± 4.4 km in total, with 6.7 ± 0.6 km and 1.9 ± 0.3 km covered at the higher intensities (≥19.0 & ≥23.0 km · h -1 ), respectively. The top five ranked teams from a high-intensity running perspective (Zambia, Spain, Brazil, Canada, Denmark) covered 24–44% more distance than the bottom five ranked teams (Jamaica, Columbia, Costa Rica, Switzerland, Vietnam) at the tournament ( P < 0.01; Effect Size [ES]: 2.3–2.5). Match-to-match variation of teams revealed Italy and Panama were particularly consistent for the distances covered at higher intensities (Coefficient of Variation [CV]: 0.3–4.5%), while Costa Rica demonstrated considerable variation (CV: 23.4–40.7%). Teams generally covered more total distance on a per-minute basis in the first versus the second half ( P < 0.01; ES: 1.1), but no differences existed at higher intensities ( P > 0.05; ES: 0.1–0.2). Correlations were found between the number of high intensity runs and various phase of play events for defensive transitions and recoveries, in addition to progressions up the pitch and into the final third ( r = 0.48–0.88; P < 0.01). A basic comparative analysis revealed Spain demonstrated the most pronounced increase (2015 = 9 th , 2019 = 35 th , 2023 = 90 th percentile; CV: 92.6%) and China PR the most marked decrease (2015 = 22 nd , 2019 = 30 th , 2023 = 0 percentile; CV: 89.6%) in their sprinting percentile rank across the last three FIFA Women’s World Cups. The present findings provide a depiction of the current collective demands of international women’s football. This information could be useful for practitioners to benchmark team performances and to potentially understand the myriad of contextual factors impacting physical performances.